Genetic diversity of two Brazilian populations of the Pampas deer (Ozotoceros bezoarticus, Linnaeus 1758) - Rodrigues,FP. (2007)
The Pampas deer (Ozotoceros bezoarticus) is one of the most endangered Neotropical cervid with populations that have been drastically reduced to small and isolated ones, mainly because of its habitat destruction. Random amplified polymorphic DNA (RAPD) markers were used to analyze population divergence and genetic variation within and between two populations corresponding to distinct subspecies. The RAPD markers displayed substantial genetic variation with all animals possessing unique RAPD phenotypes over 105 polymorphic bands produced by 15 primers. An analysis of molecular variance (AMOVA) and a neighbor-joining cluster analysis were performed to assess levels of differentiation between populations. No differentiation was recorded and about 96.0% (P < 0.00001) of the total variance was attributable to variation within populations. This result is quite distinct from data obtained by the analysis of the mtDNA control region, and is discussed on the basis of genetic differences between the different markers and the male-biased dispersal patterns generally observed in the mammal species. The data presented herein are potentially useful for future taxonomic and genetic studies in this species, for the monitoring of the genetic variation observed within these populations, and for the development of management guidelines for its conservation.